The structure of employment centres in the metropolitan region of Santiago (Chile): spacial and funcional centralization - Severino Escolano Utrilla; J. Ortiz Véliz; R. Moreno Mora (Boletín de la Asociación de Geógrafos Españoles)
Texto resumen.